Queering Multispecies Bonding: Reading Donna Haraway’s Dog Stories as Queer Feminism - Irni, Kuura (Humanimalia, 2020)
By conducting a queer theoretical reading of Donna Haraway’s work on dogs, this paper develops queer feminist animal studies by focusing on the critique and rethinking of anthropocentric family and relationship norms. Starting with Haraway’s proposal in Staying with the Trouble to “make kin, not babies” and to question the link between genealogy and kin, this paper reads Haraway’s dog stories as queer feminism. The paper argues that Haraway’s thinking aligns with queer feminist scholarship that questions the link between sex and reproduction also in nonhuman animal lives and that recognizes the value of alternatives to compulsory sexuality and couple normativity, such as Angela Willey’s ethics of antimonogamy. By conceptualizing a romantic, non-sexual relationship with a dog, Haraway’s texts destabilize normative ideals of significant relationships between adults and present an alternative to the anthropocentric understandings of intimacy and family. The paper suggests that initiating a discussion about these alternative relationship constellations in the context of feminist animal studies makes it possible to build connections between critical perspectives in animal studies and queer and sexuality studies in order to develop alternatives to couple normative, racialized, class-based, and anthropocentric family and relationship norms.